Effect of Impairment‐Testing Disclosures on the Cost of Equity Capital. (10th May 2015) - Paugam, Luc; Ramond, Olivier
Abstract Information risk – the uncertainty regarding the parameters of the distribution of firms' future cash flows – generates valuation errors and is costly to investors who require a higher return to compensate for greater information risk. We argue that, on average, through their impairment‐testing disclosures, managers convey information that reduces information risk. Using disclosures from firms included in the SBF 250 index of Euronext Paris over the period 2006–2009, we document a negative association between impairment‐testing disclosures and implied cost of equity capital. We find that prospective entity‐specific impairment‐testing disclosures are negatively associated with cost of capital whereas descriptive disclosures exhibit no association with cost of capital. Additionally, we document that firms which avoid booking impairments when low performance indicators suggest a greater likelihood of impairments exhibit no association between impairment‐testing disclosures and cost of capital. This suggests that those firms' disclosures are perceived as less accurate by investors. We also find that prospective impairment‐testing disclosures are negatively related to analysts' forecast errors. Our study adds to the literature on the economic consequences of financial reporting and sheds light on the consequences of one accounting mechanism, namely impairment‐testing disclosures, ensuring conservatism of financial reporting.